Peran Pola Pengelolaan Budaya Kerja Organisasi pada Perusahaan - Richard A. M. Napitupulu; Sunday Ade Sitorus; SUNDAY ADE SITORUS (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2025)
This community service activity aims to improve the understanding and implementation of organizational work culture at PT Aras Bina Energi in order to create a more productive and harmonious work environment. This program is carried out through three main stages, namely socialization, technical training, and assistance in implementing organizational work culture. Initial socialization was conducted to raise the awareness of leaders and employees regarding the importance of work culture in supporting organizational effectiveness. Furthermore, technical training was provided to equip employees with skills in adopting work culture values that are in accordance with organizational characteristics. The final stage was assistance in implementing the work culture, with monitoring and evaluation to ensure the sustainability of positive changes. The results showed that employees' understanding of work culture increased from 40% to 85% after socialization. The implementation of a more adaptive work culture also had an impact on increasing compliance with company regulations, reducing the rate of late work from 18% to 7%, and increasing employee productivity. In addition, changes in a more democratic leadership style improved work motivation and employee satisfaction, with satisfaction scores increasing from 3.2 to 4.1 on a scale of 5. This program demonstrates that systematic and sustainable management of an organization's work culture can have a positive impact on its employees